2015
DOI: 10.1039/c5ra06783a
|View full text |Cite
|
Sign up to set email alerts
|

Stabilization of [poly(allylamine)–tannic acid]n multilayer films in acidic and basic conditions after crosslinking with NaIO4

Abstract: Interaction of NaIO4 with (PAH–TA)n films: stabilization in strong acid and basic solutions and changes in the film permeability.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 18 publications
(9 citation statements)
references
References 19 publications
0
8
1
Order By: Relevance
“…In addition, the intrinsic autoxidation in aqueous solution can initiate the polymerization of polyphenolic molecules that enables the coating formation. , The oxidation of phenolic hydroxyl groups by dissolved oxygen forms quinones and semiquinones, which couple via secondary interactions, such as hydrogen bonding, interaction of electron donor–acceptor systems (π-stacking), or proceed to form primary bonds . In the latter case, new inter- and intramolecular C–C and C–O bonds are formed via a cascade of radical reactions. , …”
Section: Introductionmentioning
confidence: 99%
“…In addition, the intrinsic autoxidation in aqueous solution can initiate the polymerization of polyphenolic molecules that enables the coating formation. , The oxidation of phenolic hydroxyl groups by dissolved oxygen forms quinones and semiquinones, which couple via secondary interactions, such as hydrogen bonding, interaction of electron donor–acceptor systems (π-stacking), or proceed to form primary bonds . In the latter case, new inter- and intramolecular C–C and C–O bonds are formed via a cascade of radical reactions. , …”
Section: Introductionmentioning
confidence: 99%
“…The deposition of (PAH-TA) n films (5min per adsorption and rinsing step as in ref. [12]) was characterized by means of UV-vis spectroscopy (Figure 2) and by contact angle goniometry (Figure 3). The film growth is of linear type, meaning that the absorbance increases at λ=300nm, due to TA (PAH does not absorb light above λ=200nm), scales in proportion to the number of deposited layer pairs (Figure 2).…”
Section: Resultsmentioning
confidence: 99%
“…The morphology of the (PAH-TA) n films has also been characterized by means of Atomic Force Microscopy and some typical images acquired in the contact mode and in the dry state can be found in Figure 4 of ref. [12]. The (PAH-TA) n films display some antioxidant activity as quantified through a decrease in absorbance at λ=517nm, typical of the transformation of the purple DPPH into the yellowish DPPH-H (Figure 1).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…In the current study, incorporation of the tested polyphenols was performed into the base part (Table 1) of the epoxy resin-based sealer. We believe that since the catalyst part of the epoxy resin contains amines, oxidation of PY could have activated the polymerization and/or reduced beneficial effects of the phenolic compounds via formation of covalent bonds with the amines [23]. One of the first outcomes obtained in this study was that the control (free of polyphenols) sealer had some antibacterial effects against E. faecalis after 24 h. Ruiz-Linares et al [24] analyzed an epoxy resin-based sealer (AH-Plus, Dentsply Sirona, Konstanz, Germany) against E. faecalis and they showed that such material could induce some antibacterial effects as a result of the release of formaldehyde and/or other toxic non-polymerized components, such as amines or epoxy monomers.…”
Section: Discussionmentioning
confidence: 99%